2012
DOI: 10.1590/s0102-695x2011005000219
|View full text |Cite
|
Sign up to set email alerts
|

Anticholinesterase activity evaluation of alkaloids and coumarin from stems of Conchocarpus fontanesianus

Abstract: Abstract:Conchocarpus fontanesianus (A. St.-Hill.) Kallunki & Pirani, Rutaceae, popularly known as pitaguará, is a native and endemic tree from São Paulo and Rio de Janeiro States, Brazil. Based in the information that anticholinesterasic derivatives could act as new prototypes to treatment of Alzheimer disease, this work describes the fractionation guided by evaluation of the anticholinesterase activity of the ethanolic stems extract from C. fontanesianus. This procedure afforded the alkaloids dictamnine (1),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 24 publications
0
17
0
1
Order By: Relevance
“…This alkaloid fraction was also analyzed via HPLC. In this work, in the stem material, the presence of dictamnine (1), skimmianine (2), γ-fagarine (3), 2-phenyl-1-methyl-quinoline and marmesine was confirmed [6].…”
Section: Extraction Of Furoquinoline Alkaloids From Rutaceae Family Pmentioning
confidence: 50%
See 3 more Smart Citations
“…This alkaloid fraction was also analyzed via HPLC. In this work, in the stem material, the presence of dictamnine (1), skimmianine (2), γ-fagarine (3), 2-phenyl-1-methyl-quinoline and marmesine was confirmed [6].…”
Section: Extraction Of Furoquinoline Alkaloids From Rutaceae Family Pmentioning
confidence: 50%
“…St.-Hill.) Kallunki&Pirani, by Cabral et al [6], have been shown to have inhibitory activity towards acetyl cholinesterase. In this study, skimmianine (2) was shown to be more active.…”
Section: The Biological Activity Of Furoquinoline Alkaloidsmentioning
confidence: 98%
See 2 more Smart Citations
“…In our opinion, there is a clear trend towards the use of the TLC bioautography technique as a method for screening active compounds against microorganisms rather than a method for the detection of enzyme activities or inhibitors. The use of TLC (bio)autography was reported for the screening of inhibitors of acetylcholinesterase [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] , butyrylcholinesterase 12,16,22,23,27 , dipeptidyl peptidase IV 28 , glucose-6-phosphate dehydrogenase 29 , a-and b-glucosidases [30][31][32][33][34] , lipase [35][36][37] , monoamine oxidases A and B 38,39 , DNA topoisomerase I 40 , tyrosinase [41][42][43] and xanthine oxidase 44 . To date, the use of the TLC-based autographic method for the detection of PGI inhibition has only been developed for a biocatalyst isolated from the reference E. coli strain ATCC (American Type Culture Collection) 25922 45 .…”
Section: Introductionmentioning
confidence: 99%